In patients with primary Sjögren’s syndrome innate-like MAIT cells display upregulated IL-7R, IFN-γ, and IL-21 expression and have increased proportions of CCR9 and CXCR5-expressing cells - Hinrichs, Anneline C.; Kruize, Aike A.; Leavis, Helen L.; van Roon, Joel A. G. (Frontiers in Immunology, 2022)
Introduction Mucosal-associated invariant T (MAIT) cells might play a role in B cell hyperactivity and local inflammation in primary Sjögren’s syndrome (pSS), just like previously studied mucosa-associated CCR9+ and CXCR5+ T helper cells. Here, we investigated expression of CCR9, CXCR5, IL-18R and IL-7R on MAIT cells in pSS, and assessed the capacity of DMARDs to inhibit the activity of MAIT cells. Methods Circulating CD161+ and IL-18Rα+ TCRVα7.2+ MAIT cells from pSS patients and healthy controls (HC) were assessed using flow cytometry, and expression of CCR9, CXCR5, and IL-7R on MAIT cells was studied. Production of IFN-γ and IL-21 by MAIT cells was measured upon IL-7 stimulation in the presence of leflunomide (LEF) and hydroxychloroquine (HCQ). Results The numbers of CD161+ and IL-18Rα+ MAIT cells were decreased in pSS patients compared to HC. Relative increased percentages of CD4 MAIT cells in pSS patients caused significantly higher CD4/CD8 ratios in MAIT cells. The numbers of CCR9 and CXCR5-expressing MAIT cells were significantly higher in pSS patients. IL-7R expression was higher in CD8 MAIT cells as compared to all CD8 T cells, and changes in IL-7R expression correlated to several clinical parameters. The elevated production of IL-21 by MAIT cells was significantly inhibited by LEF/HCQ treatment. Conclusion Circulating CD161+ and IL-18Rα+ MAIT cell numbers are decreased in pSS patients. Given their enriched CCR9/CXCR5 expression this may facilitate migration to inflamed salivary glands known to overexpress CCL25/CXCL13. Given the pivotal role of IL-7 and IL-21 in inflammation in pSS this indicates a potential role for MAIT cells in driving pSS immunopathology.